2015
DOI: 10.1177/1475240915570548
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the international educator and the strategic role of critical incidents

Abstract: This study explored the characteristics of the international educator through a qualitative analysis of initial decisions to teach abroad. Using interview data from 30 Anglophone educators based across three international schools in China and the Netherlands, the investigation looked beyond surface motives to explore the deeper values which propelled educators overseas. Dominant characteristics included a high value ascribed to travel, as well as a high value ascribed to change and/or risk. How international e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
3
28
0
Order By: Relevance
“…For example, Tyron's and Robert's narratives clearly showed evidence of the international teacher as a denizen or a global migrant, whilst Nora's narrative presented being an international teacher in terms of permanent liminality, which leads to anxiety and a sense of uncertainty. These findings support previous research studies (Savva, 2015(Savva, , 2017 that focus on the difficulties of teaching in international schools. Another significant finding is the prevalence of what could be called a 'them and us' discourse which is most vividly seen in Robert's and Nora's narratives, in which school leadership is positioned as the negative part of a binary opposition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, Tyron's and Robert's narratives clearly showed evidence of the international teacher as a denizen or a global migrant, whilst Nora's narrative presented being an international teacher in terms of permanent liminality, which leads to anxiety and a sense of uncertainty. These findings support previous research studies (Savva, 2015(Savva, , 2017 that focus on the difficulties of teaching in international schools. Another significant finding is the prevalence of what could be called a 'them and us' discourse which is most vividly seen in Robert's and Nora's narratives, in which school leadership is positioned as the negative part of a binary opposition.…”
Section: Discussionsupporting
confidence: 91%
“…Recent articles (Bailey, 2015;Blyth, 2017;Bunnell, 2016Bunnell, , 2017Burke, 2017;Cavendish, 2011;Halicioglu, 2015;Poole, 2017Poole, , 2018Savva, 2015Savva, , 2017 and books (Arber, Blackmore, & Vongalis-Macrow, 2014;Minor & Duncan, 2017) that explore IETs may offer some suggestions. This burgeoning literature tends to be either practitioner-or researcher-focused.…”
Section: International Education Teachers As An Educational Precariatmentioning
confidence: 99%
“…Importantly, this dissonance does not necessarily produce negative outcomes. On the contrary, research studies have found that it is through experiences of dissonance and disequilibrium that increased intercultural awareness among students and faculty often materializes (Allan, 2002; Savva, 2015 and 2017A). In the case of teachers, research has found that the experience of dissonance can produce definitive changes in actual teaching methods used in classroom settings (Savva, 2017B).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous attempts to develop typologies of international school teachers (e.g., Hardman, 2001; Garton, 2000) have been critiqued (e.g. Savva, 2015) for being ‘insufficiently nuanced to capture this group’s motivations and identities’ (Bailey & Cooker, 2019, p. 129). Fortunately, the last few years have seen a growing interest in the lives and experiences of teachers in international schools (Arber et al, 2014; Bailey, 2015; Blyth, 2017; Bunnell, 2016, 2017), which could be likened to something of an international school teacher turn in the field of international education.…”
Section: Introductionmentioning
confidence: 99%